Analisis Miskonsepsi Pada Materi Kesetimbangan Dalam Asam Basa Dan Hidrolisis Garam - Asep Hidayat Amin, Muhamad; Asworo, Yuliana Dwi; Rahmawati, Yuli; Irwanto (Jurnal Riset Pendidikan Kimia (JRPK), 2023)
This study aims to analyze students' misconceptions about acid-base equilibrium and salt hydrolysis using instruments from [1]. This research is descriptive-quantitative, and the subjects of this study were students of classes XI and XII MIPA at one of the State Madrasah Aliyah in west Jakarta in the 2022/2023 school year. Data was collected using the two-tier multiple-choice web-based misconception diagnostic test. Based on the results of the study, it was found that in class XI, there were 80% of students who did not understand and 15% of students had the wrong concept on acid-base material, while in class XII, 72% did not understand and 24% of students had the wrong concept on acid-base material. The answers with the most misconceptions were found in acid-base question number 4, where 76% of students cannot choose which, ionic group can be together with a solution that is at room temperature under conditions of H+ ion concentration in a solution ionized by water of 1 x 10–13 mol/L and the reason for the proper explanation. Students tend to only understand what acid-base or hydrolysis salts are without strengthening their deeper concepts.